Recent Updates on DTD (D-Tyr-tRNATyr Deacylase): An Enzyme Essential for Fidelity and Quality of Protein Synthesis - Bhatt, Tarun K.; Soni, Rani; Sharma, Drista (Frontiers in Cell and Developmental Biology, 2016)
During protein synthesis, there are several checkpoints in the cell to ensure that the information encoded within genetic material is decoded correctly. Charging of tRNA with its cognate amino acid is one of the important steps in protein synthesis and is carried out by aminoacyl-tRNA synthetase (aaRS) with great accuracy. However, due to presence of D-amino acids in the cell, sometimes aaRS charges tRNA with D-amino acids resulting in the hampering of protein translational process, which is lethal to the cell. Every species has some mechanism in order to prevent the formation of D-amino acid-tRNA complex, for instance DTD (D-Tyr-tRNA deacylase) is an enzyme responsible for the cleavage of ester bond formed between D-amino acid and tRNA leading to error free translation process. In this review, structure, function and enzymatic mechanism of DTD are discussed. The role of DTD as a drug target is also considered.